![\sqrt{3x { }^{2} } - \sqrt{2x} + 3 \sqrt{3} = 0 \sqrt{3x { }^{2} } - \sqrt{2x} + 3 \sqrt{3} = 0](https://tex.z-dn.net/?f=+%5Csqrt%7B3x+%7B+%7D%5E%7B2%7D+%7D++-++%5Csqrt%7B2x%7D++%2B+3+%5Csqrt%7B3%7D++%3D+0)
Answers
Answered by
0
Given : √(3x²) - √(2x) + 3√3 = 0
or √3x² - √2x + 3√3 = 0
To Find :
Solution:
√(3x²) - √(2x) + 3√3 = 0
=> √3√x² - √2√x + 3√3 = 0
=> √x = (- (- √2) ± √( (√2)² - 4√3 3√3) )/2√3
=> √x = (√2 ±√(-34) )/2√3
=> √x = (√2 ± i√34 )/2√3
if
√3x² - √2x + 3√3 = 0
=> x = (√2 ± i√34 )/2√3
Learn More:
if alpha +beta are the roots of equation 4x²-5x+2=0 find the equation ...
https://brainly.in/question/8333453
Show that the roots of equation (xa)(xb) = abx^2; a,b belong R are ...
https://brainly.in/question/21009259
Similar questions